Sustainability considerations in membrane-based technologies for industrial effluents treatment - Kamali, Mohammadreza (2019)
Treatment of industrial effluents (EFs) from the polluted wastewater sources using membrane technologies is an effective and attractive alternative to overcome the weaknesses of some of the conventional wastewater treatment processes, especially when dealing with EFs loaded with recalcitrant organic pollutants and toxic substances. The application of various polymeric and inorganic membrane based technologies to be used for the treatment of industrial EFs has attracted a considerable attention in the past decades. In this regard, a critical discussion on the sustainability of various aspects of membrane technologies would promote the commercialization of these technologies. In this review, various sustainability criteria in technical, economic, environmental, and social categories have been considered for a critical discussion on the current status and improvement opportunities of membrane technologies for the treatment of industrial EFs. While the application of polymeric membranes has been restricted by some bottlenecks to deal with some industrial effluents, metal oxides fabricated ceramic membranes, and especially those fabricated with nanostructured materials such as nano-zeolites, those made of metal organic frameworks as well as carbon-based fabricated membranes have shown a promising performance in the rejection of recalcitrant organic pollutants. In addition, the combinations of inorganic membrane technologies with other novel methods such as advanced oxidation processes (e.g., using engineered nanomaterials) can be considered among the best options to deal with such highly polluted effluents.